2011
DOI: 10.1007/s10822-011-9455-8
|View full text |Cite
|
Sign up to set email alerts
|

In silico identification of new ligands for GPR17: a promising therapeutic target for neurodegenerative diseases

Abstract: GPR17, a previously orphan receptor responding to both uracil nucleotides and cysteinyl-leukotrienes, has been proposed as a novel promising target for human neurodegenerative diseases. Here, in order to specifically identify novel potent ligands of GPR17, we first modeled in silico the receptor by using a multiple template approach, in which extracellular loops of the receptor, quite complex to treat, were modeled making reference to the most similar parts of all the class-A GPCRs crystallized so far. A high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 54 publications
(76 citation statements)
references
References 43 publications
4
72
0
Order By: Relevance
“…The purinergic component of GPR17 has been confirmed in two additional independent studies [17,18], whereas response to cysteinyl-leukotrienes has been proposed to be related to the formation of heteromers [17,[19][20][21]. In this respect, in a previous in silico and in vitro study on GPR17 ligands performed by our group [22], we proposed a possible allosteric effect of the CysLT1R antagonist montelukast on GPR17 uracil ligands, suggesting that montelukast may act on a yet uncharacterized binding site differing from the principal orthosteric one.…”
Section: Introductionmentioning
confidence: 70%
“…The purinergic component of GPR17 has been confirmed in two additional independent studies [17,18], whereas response to cysteinyl-leukotrienes has been proposed to be related to the formation of heteromers [17,[19][20][21]. In this respect, in a previous in silico and in vitro study on GPR17 ligands performed by our group [22], we proposed a possible allosteric effect of the CysLT1R antagonist montelukast on GPR17 uracil ligands, suggesting that montelukast may act on a yet uncharacterized binding site differing from the principal orthosteric one.…”
Section: Introductionmentioning
confidence: 70%
“…Benned-Jensen and Rosenkilde (23) report a different agonist profile for nucleotide ligands but failed to recapitulate activation by CysLTs, a finding that is in line with other studies that reported lack of agonist activity altogether (20-22, 24) as well as our data in this study. Nevertheless, even a set of five small-molecule agonists identified by virtual screening and proposed to activate GPR17 with high potency (ASINEX ligands 1 to 5) (32) was inactive in our hands and has not been more widely used as research tool for this receptor. Clearly, the pharmacology and function of GPR17 remain rather contentious issues that need to be resolved with a ligand that reliably and reproducibly activates GPR17.…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, they are in line with the vision of the 21 st century toxicity paradigm: chemicals will be subjected to a multiplicity of high-throughput screening tests to detect cellular response to an array of “pathways of toxicity”, and results will feed into computational systems biology tools that model dose-response effects and inform new risk assessment approaches [7]. Several computational approaches may be useful for evaluating interactions between a receptor and its putative ligands: some of them are based on molecular docking, which has been reliably used for decades in pharmacological research and development [8], [9].…”
Section: Introductionmentioning
confidence: 99%